MUSLIM AWARENESS IN SCIENCE OF FARAIDH SYSTEMS - Khifni Kafa Rufaida (UNISSULA, 2019)
Islamic Inheritance Law basically applies to all Muslims in the world. But in fact, a true Muslim society must obey Mawaris jurisprudence is actually more leave even forget this science. Because it is no longer a concern for Muslims, finally arose some disputes between families which is really due to the neglect of science faraidh which has been arranged by God for the benefit of his people. It is important for the writer to contribute how to build awareness of the existence of Muslim faraidh science in the division of inheritance system. In this study, the method used to address the problem is normative. Methods of data collection in this research is done by: Library Researchand Field Research. The analytical methods used this research is qualitative analysis method. Awareness of the importance of the science of inheritance can be grown in a way memperlajari faraidh science. By studying faraidh will automatically raise awareness faraidh to apply science in the division of the inheritance. The author argues that this faraidh science should be included in a curriculum in Madrasah Diniyyah. The principle of peace is a justifiable manner, so that the atmosphere can be established brotherhood. Throughout the peace was not meant to proscribe lawful or justify the unlawful, then it is allowed. The author thinks that the lack of public knowledge about the law faraidh a major cause of the low awareness of the use of science in the division of islamic inheritance/faraidh.